A study of students' achievement in algebra: Considering the effect of gender and types of schools - Saleh, Salmiza; Abdul Rahman, Muhamad Asyraf
Algebra is a branch of mathematics that deals with symbols and also the rules for manipulating those symbols, which are used to represent numbers and quantities in mathematical formulae and equations. It is needed and used in our everyday lives. The purpose of this study was to examine students’ performance in algebra related to gender and types of schools.The research sample consisted of 317 students (135 boys and 182 girls) from three types of schools in Malaysia ie; national schools, Islamic-religious schools and boarding schools. Data were collected through an instrument known as the Algebra Achievement Test (AAT), and were then analyzed quantitatively using a two-way ANOVA test. Research findings showed that there were statistically significant main effects for gender and types of schools towards students’ achievement in algebra. However, no interactional effects were found between gender and types of schools that could influence the results obtained.It is concluded that gender and types of schools do effect students' achievement in algebra.